NATIVE LANGUAGE INTERFERENCE ON TARGET LANGUAGE WRITINGS OF INDONESIAN EFL STUDENTS: AN EXPLORATORY CASE STUDY - R. Agus Budiharto (Indonesian EFL Journal, 2019)
Possessing language students who are skilled in creating a structured, orderly and no error-found piece of composition constitutes a hope and a wish for many EFL teachers, as they are the individuals who undergo a big problem when their students commit numerous errors in EFL writing as a result of their native language interference. This study is aimed at exploring native language influence on students’ English writings as well as investigating the salient and common grammatical errors in their writing with the purpose of checking whether or not Indonesian as the students’ L1 influence them when writing in English. To this end, a corpus of 22 English essays written by students is examined and the errors are then categorized according to the following aspects: grammatical, lexico-semantic, mechanics, and word order sorts of errors. In this study, mixed methods research designs are used: quantitative and qualitative. The results revealed that UNIRA students commit different sorts of errors which are chiefly on account of their native language (Indonesian) interference. The students highly rely on their L1 in stating their thoughts, even though the ranking processes revealed that their essays hold different sorts of errors, those in the grammar and the lexico-semantic statistically constitute the most serious and recurrent ones.Keywords: grammatical sentence; L1 interference; lexico-semantic; writing.